Private Power Financing : From Project Finance to Corporate Finance - Jechoutek, Karl G. (World Bank, Washington, DC, 2012)
Project financing of independent power producers (IPPs) may seem the only solution to the intractable problem of getting private credit to the power sector. In the developing world, however, the public-private partnership in project-financed IPP ventures has been slow to produce results. To achieve substantive progress in IPP financing, limited recourse project financing will have to evolve toward structures with greater balance sheet support. First, balance sheet support by the main partners in an IPP financing offers greater security to lenders and provides easier access to long-term debt. Second, balance sheet support by IPP sponsors can open access to public equity markets, which are deeper and generally cheaper. Third, increased corporate balance sheet support is a corollary to the restructuring in the world s power sectors. Greater corporate finance support will make it possible to raise private capital for independent power financing from wider, deeper, and cheaper sources. This Note recommends the following strategies: 1) Encourage the formation of large, well-capitalized independent generation companies. 2) Encourage divestiture of commercially operating generation plants by incumbent utilities to IPP developers. 3) In IPP prequalification under competitive bidding, give greater weighting to IPP developers with business listed on a stock exchange and to those with well-capitalized balance sheets. 4) Encourage project sponsors to use balance sheet support for the financing plan in order to increase corporate financing.